Polygyny among the Yoruba muslims of South Western Nigeria : a critical study - Kayode, Adeyemo Lateef (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2012)
This study examines the practice of polygyny among the Yoruba Muslims of South Western Nigeria with a view to ascertain how they perceive it, how it is being practised by them, the Islamicity or otherwise of such practice, its impacts on the Yoruba polygynious Muslim families, the influence of the local customs and tradition on the practice or the praxis, differential in the male/female perception of polygyny as well as the factors influencing the perception and practice among them. Polygyny is a controversial issue not only among non-Muslims but equally among Muslims. The thesis therefore, in addition to the basic focus earlier mentioned, examines the conflicting views held by Muslims about the permissibility of polygyny. The findings reveal that polygyny is allowed by Islam particularly under certain circumstances in order to safeguard society against the evils of promiscuity and its allied problems. The issue of justice forms the major bone of contention as Allah says that Muslims (men) would not be able to treat women equally, even if it is their ardent desire to do so. Attempt is therefore made to examine Islamic principles of justice and how it affect polygyny permitted by it (Islam) as well as how far are Yoruba Muslim polygynious men dispensing it. Being a phenomenological research, mixed method is adopted since it is generally accepted to be the most suitable one for this kind of inquiry. Interview, Focus Group Discussion (FGD) and questionnaire are used as media for data collection much as library collections, government gazettes and archival materials are used where and when necessary. Although, the practice is found to have been helpful most especially with regards to the care of widows, divorcees and those of over stayed distressed spinsters ridding the society of whoredom or promiscuity, yet it has not been without some shortcomings which include but are not limited to lack of proper understanding of Islam, poverty, juvenile delinquency, injustice, enmity and conflicts among wives. Recommendations on how to solve the identified shortcomings or problems are made while suggestions for further studies are equally given.